For an immoral literature for the «law and literature» movement - Arancibia Hurtado, Camilo (2021)
A theoretical consideration in law and literature studies, which are advancing in our continent, is what kind of literature we will analyze in this discipline. For this paper, I will make use of two studies by the writer D. H. Lawrence on the painter Paul Cézanne, which explore the forms of static representation of reality based on Kodak photography and the reproduction of clichés in art, both characteristic of moral art, against which Cézanne’s immoral art stands up, characterized by its relational dynamism and its struggle against stereotypes. The moral art can be countered in our field with Bakhtin’s notions of polyphony, associated with relational dynamism, and Luque’s hymenopterous art, linked to stereotypes. In doing so, I hope to give an account of how an immoral literature can help us illuminate the juridical problems that afflict human beings.